Access to justice : a critical analysis of recoverable conditional fees and no-win no-fee funding - Peysner, John; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This book addresses an experiment in funding money damage claims in England from 2000 to 2013. The model - recoverable conditional fees - was unique and has remained so. It covers the development, amendment and effective abolition of the model, as well as the process of policy development and the motivation and objectives of the policy makers.
Keywords: Contingent fees -- England